New insights into human hair: SAXS, SEM, TEM and EDX for Alopecia Areata investigations - Adina Coroaba; Anca E. Chiriac; Liviu Sacarescu; Tudor Pinteala; Bogdan Minea; Sorin-Alexandru Ibanescu; Mihaela Pertea; Aurelian Moraru; Irina Esanu; Stelian S. Maier; Anca Chiriac; Mariana Pinteala (PeerJ, 2020)
Background Alopecia areata (AA) is a T-cell-mediated autoimmune disease and affects up to 2% of the population. There is a need for a more profound and rigorous understanding of the structure and composition of human hair affected by AA in order to manage this disease. The aim of this article is to understand the effects of AA on the structure and composition of human hair. Methods Several physico-chemical investigation methods, such as Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Energy-Dispersive X-ray Spectroscopy (EDX), and microbeam Small Angle X-ray Scattering (SAXS), were used to analyze human hair samples obtained from healthy donors and patients with AA. Results SEM revealed more severe hair surface defects for the white regrown hair (W-AA) samples. TEM showed the presence of air-like vesicles located in the endocuticle of regrown hair. Analysis of ultrathin sections of W-AA showed the existence of empty vesicles and smaller melanin granules compared to control samples. SAXS demonstrated that unaffected hair of patients with AA (B-AA) and W-AA melanin aggregates are different in their sizes and shapes compared to the control samples. EDX data showed that W-AA elemental composition was significantly different from the other sample groups. Our study showcases promising non-invasive techniques for a better and more accurate understanding of changes in the internal structure and composition of hair affected by AA.